2008
DOI: 10.1142/s0218625x08011743
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of the Antimicrobial 4-Amino-Decylpyridinium Bromide Cationic Surfactant

Abstract: 4-Amino-decylpyridinium bromide (ADPBr), an antimicrobial surface active agent, was synthesized by quaternization of 4-aminopyridine (AP) with decyl bromide (DBr). The reaction was carried out at 1:1.2 molar ratio of reactants (4-aminopyridine and decyl bromide, respectively) at 200°C for 10 min. The maximum yield of the product was 74.6%. The structure of the synthesized product was characterized by using modern analytical techniques, such as FT-IR, 1 H NMR, and 13 C NMR. The antimicrobial activity of the sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In a related study, 4-amino-1-dodecylpyridinium chloride was found to have antimicrobial activity against E. coli and Staphylococcus aureus (Zhao and Sun, 2008). Good antimicrobial activity was observed for 4-aminodecylpyridinium bromide against E. coli, only at very high concentration, 600 ppm (Madaan and Tyagi, 2008).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In a related study, 4-amino-1-dodecylpyridinium chloride was found to have antimicrobial activity against E. coli and Staphylococcus aureus (Zhao and Sun, 2008). Good antimicrobial activity was observed for 4-aminodecylpyridinium bromide against E. coli, only at very high concentration, 600 ppm (Madaan and Tyagi, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…These methods have some drawbacks such as the need for protection of free -NH 2 group (Zhao and Sun, 2006) low yield (Obando et al, 2009;Zhao and Sun, 2006) and the use of high temperature (Madaan and Tyagi, 2008). Of late, it is well established that the quaternization on endocyclic nitrogen is easier than exocyclic nitrogen due to higher proton affinity of the endocyclic nitrogen (Pillay et al, 1997;Kas'yan et al, 2005).…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations